Effectiveness of a harmonica-integrated, tele-supervised home-based pulmonary rehabilitation program on lung function and comprehensive health outcomes in patients with chronic obstructive pulmonary disease: a randomized controlled trial protocol - Zeng, Qiuxuan; Lin, Xiaohong; Chen, Wenli; Fong, Daniel Yee Tak; Li, Junxin; Li, Jiaying (Frontiers in Public Health, 2025)
IntroductionHarmonica playing mimics pursed-lip breathing and strengthens respiratory muscles. Combined with music therapy, it may improve both pulmonary and mental health in chronic obstructive pulmonary disease (COPD) patients, though its effects are not well understood. This protocol outlines a randomized controlled trial (RCT) to evaluate the effectiveness of integrating harmonica playing into pulmonary rehabilitation (PR) programs.Methods and analysisThis single-center, two-arm RCT will be conducted at a tertiary hospital in Guangzhou, China. A total of 248 adult patients (with a clinical diagnosis of COPD but without severe comorbidities, significant cognitive impairments, and prior experience with the intervention components) will be randomized in a 1:1 ratio to either a harmonica-integrated PR group (intervention) or a standard PR group (control) for 6 months of home-based, tele-supervised training. The intervention will incorporate harmonica sessions in addition to standard PR exercises (breathing and physical exercises). Both groups will undergo in-hospital training sessions, supplemented by daily home practice under remote supervision by PR staff. The primary outcome is lung function (measured by FEV1%), while secondary outcomes include respiratory muscle strength, exercise capacity, fatigue, dyspnea, symptom burden, mental health, self-efficacy, quality of life, social support, adherence, and patient satisfaction. Statistical analyses will employ mixed-effects models with an intention-to-treat approach.ConclusionThis trial will evaluate the efficacy of a harmonica-integrated, home-based PR program with tele-supervision for COPD patients on lung function, respiratory muscle strength, exercise capacity, and overall health. If effective, it could offer a novel, affordable, and accessible home-based PR approach for COPD management.Trial registration numberClinicalTrials.gov: NCT05995847.